2020
DOI: 10.1371/journal.pone.0237102
|View full text |Cite
|
Sign up to set email alerts
|

The association between the lack of safe drinking water and sanitation facilities with intestinal Entamoeba spp infection risk: A systematic review and meta-analysis

Abstract: Intestinal protozoa infections are responsible for considerable morbidity and mortality, especially where the exposed population suffers from a lack of drinking water and sanitation facilities. In this study, the association between the lack of safe drinking water and sanitation (toilet) facilities with intestinal Entamoeba spp infection in the children (5–11 years), adult (18–55 years), and all age (5–55 years) were assessed. For this purpose, some of the international databases such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 92 publications
0
13
0
3
Order By: Relevance
“…Osman et al [ 14 ] reported that the consumption of untreated water triples the risk of protozoal infections compared to water treated with chlorite. In addition, the consumption of uncooked fruits and vegetables after washing with contaminated water tends to also increase the risks of intestinal protozoan infections [ 23 ], as well as limited access to clean water and adequate sanitation facilities such as toilets [ 24 ]. Similarly, extreme poverty and low economic level are also predictors for protozoal infections occurrence [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osman et al [ 14 ] reported that the consumption of untreated water triples the risk of protozoal infections compared to water treated with chlorite. In addition, the consumption of uncooked fruits and vegetables after washing with contaminated water tends to also increase the risks of intestinal protozoan infections [ 23 ], as well as limited access to clean water and adequate sanitation facilities such as toilets [ 24 ]. Similarly, extreme poverty and low economic level are also predictors for protozoal infections occurrence [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perbedaan hasil tersebut diduga karena letak geografis, sanitasi kandang dan sistem pemeliharaan babi pada masing-masing peternakan berbeda. Atabati et al (2020) menyatakan bahwa faktor tempat dan cara pemeliharaan yang berbeda pada suatu peternakan berimplikasi terhadap tingkat prevalensi infeksi Entamoeba sp., di samping itu, faktor lingkungan (kontaminasi tinja di lingkungan), standar kebersihan dan sanitasi yang buruk berhubungan dengan infeksi parasit usus termasuk infeksi Entamoeba spp. sangat terbatas.…”
Section: Hasil Dan Pembahasanunclassified
“…Potential risk factors for the prevalence of Entamoeba spp. are hygiene, socioeconomic, exposure to human and animal waste, and household wastewater (Ben-Ayed et al 2017;Atabati et al 2020). Desowits (1986) reported cases of amoebiasis in children caused by E. polecki (19%) in Papua New Guinea and estimated that pigs were the source of transmission to humans because of the close relationship between humans and pigs, and supported by poor sanitation.…”
Section: Resultsmentioning
confidence: 99%